Hubungan Self Esteem dengan Perilaku Narsistik Pengguna Media Sosial Kelas XI SMAN 6 Kota Bogor - Hanifah Nurismiati; Rusdi Kasman; Falizar Rivani (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
This study aims to determine the relationship between self-esteem and narcissistic behavior in adolescent social media users. The research method used is quantitative with a correlational design. The study population was 359 high school students, with a sample of 188 students selected using proportional random sampling technique. Data collection was carried out using the Rosenberg Self-Esteem Scale and the Narcissistic Scale, which have been tested for validity and reliability. Data analysis used the Pearson correlation test. The results of the study showed a significant negative relationship between self-esteem and narcissistic behavior in adolescent social media users (r = -0.235; p < 0.05), which means that the higher the self-esteem, the lower the narcissistic behavior, and vice versa. These findings are expected to be a reference for guidance and counseling teachers, schools, and parents in developing self-esteem improvement programs to minimize narcissistic behavior in adolescents